Perfectionism and attitudes towards doping in athletes: A continuously cumulating meta-analysis and test of the 2 × 2 model - Madigan, D. J.; Mallinson-Howard, S. H.; Grugan, M. C.; Hill, A. P. (European Journal of Sport Science, 2020)
Perfectionism may promote engagement in illegal and unacceptable behaviours such as doping. To examine this idea, in the present study, we had two aims. First, we re-examined the relationship between perfectionism and attitudes towards doping and, in doing so, conducted a continuously cumulating meta-analysis. Second, we extended our understanding of this relationship by providing the first test of the 2 × 2 model of perfectionism in context of doping. A sample of 181 university athletes (mean age 18.5 years) completed measures of perfectionism (evaluative concerns perfectionism [ECP] and personal standards perfectionism [PSP]) and attitudes toward doping. A continuously cumulating meta-analysis based on five studies (including the present study; N = 952) indicated that ECP showed a significant small-to-medium positive relationship with attitudes towards doping (r+ = .21), whereas PSP showed a nonsignificant small positive relationship with attitudes towards doping (r+ = .07). In addition, moderated regression analysis provided support for two hypotheses of the 2 × 2 model. Specifically, pure ECP (high ECP, low PSP) was associated with more favourable attitudes towards doping than mixed perfectionism (high ECP, high PSP) and non-perfectionism (low ECP, low PSP). The present findings suggest that ECP is a significant positive predictor of attitudes towards doping and that athletes who exhibit a combination of high ECP and low PSP are the most likely to be at risk of doping. Consequently, a focus on reducing ECP may be a valuable addition to anti-doping education programmes.